The value of cerebrospinal fluid leukocyte aggregation in distinguishing the causes of meningitis in children - Michelow, Ian C (My University, 2014)
We evaluated a previously proposed method to distinguish bacterial from viral or aseptic meningitis. Cerebrospinal fluid (CSF) samples from 109 children with meningitis (67 bacterial, 23 viral and 19 aseptic) were compared on the basis of a predefined leukocyte aggregation score (LAS). The median LAS was 32.1% (range 0-84.1%) in the bacterial group, 0% (range 0-16.6%) in the viral group and 0% (range 0-20.7%) in the aseptic group. The LAS performed better than peripheral white cell count (WCC), serum C-reactive protein and CSF WCC in diagnosing bacterial meningitis. It was equally as sensitive as CSF protein and serum TNF-a, IL-ip, IL-6 and IL-8 but inferior to a combination of blood culture, CSF Gram stain and CSF culture. Significant correlations were found between the LAS and a number of inflammatory markers. Prior antibiotics, duration of symptoms prior to admission and traumatic lumbar punctures did not effect the LAS. HIV-1 status lowered the score in viral/aseptic cases. The test may be useful as an early screening tool but its sensitivity does not surpass the currently employed methods.